CD44 single nucleotide polymorphism and isoform switching may predict gastric cancer recurrence. Issue 6 (28th September 2015) - Suenaga, Masaya; Yamada, Suguru; Fuchs, Bryan C.; Fujii, Tsutomu; Kanda, Mitsuro; Tanaka, Chie; Kobayashi, Daisuke; Fujiwara, Michitaka; Tanabe, Kenneth K.; Kodera, Yasuhiro
<x xml:space="preserve">Abstract</x> Background and Objectives The clinical implications of single nucleotide polymorphisms (SNPs) in CD44 remain unclear. This study examined the relationships of CD44 SNPs with clinicopathological parameters and prognosis in Japanese gastric cancer patients. Methods The CD44 SNPs were analyzed in 11 gastric cancer cell lines and 517 clinical specimens. The expression of CD44 standard (CD44s) and CD44 variant 9 isoform (CD44v9) transcripts were measured by quantitative real‐time polymerase chain reaction. Results The CD44 rs187116 A/A, A/G, and G/G genotypes were present in 10.3%, 45.1%, and 44.7% of patients, respectively. The presence of CD44 rs187116 A/G or G/G genotypes was significantly associated with positive peritoneal washing cytology (P = 0.012). Disease‐free survival of patients with these genotypes was significantly worse than in those with the A/A genotype (P = 0.039). Multivariate analysis showed that the CD44 rs187116 was independently prognostic of disease‐free survival (P = 0.047). The CD44s/CD44v9 ratio was significantly lower in patients with the CD44 rs187116 A/A genotype than in those with the A/G (P = 0.046) and G/G (P = 0.047) genotypes. Conclusions The CD44 rs187116 genotype could predict disease recurrence in Japanese gastric cancer patients, and the SNP was associated with CD44 isoform switching. J. Surg. Oncol. 2015;112:622–628. © 2015 Wiley Periodicals, Inc.